Treatment With Nimodipine or FK506 After Facial Nerve Repair Neither Improves Accuracy of Reinnervation Nor Recovery of Mimetic Function in Rats - Barham, Mohammed; Streppel, Michael; Guntinas-Lichius, Orlando; Fulgham-Scott, Nicole; Vogt, Johannes; Neiss, Wolfram F. (Frontiers in Neuroscience, 2022)
Purpose: Nimodipine and FK506 (Tacrolimus) are drugs that have been reported to accelerate peripheral nerve regeneration. We therefore tested these substances aiming to improve the final functional outcome of motoric reinnervation after facial nerve injury. Methods: In 18 female rats, the transected facial nerve was repaired by an artificial nerve conduit. The rats were then treated with either placebo, nimodipine, or FK506, for 56 days. Facial motoneurons were pre-operatively double-labeled by Fluoro-Gold and again 56 days post-operation by Fast-Blue to measure the cytological accuracy of reinnervation. The whisking motion of the vibrissae was analyzed to assess the quality of functional recovery. Results: On the non-operated side, 93%-97% of those facial nerve motoneurons innervating the vibrissae were double-labeled. On the operated side, double-labeling only amounted to 38% (placebo), 40% (nimodipine) and 39% (FK506), indicating severe misdirection of reinnervation. Regardless of postoperative drug or placebo therapy, the whisking frequency reached 83%-100% of the normal value (6.0 Hz), but whisking amplitude was reduced to 33-48% while whisking velocity reached 39-66% of the normal values. Compared to placebo, statistically neither nimodipine nor FK506 improved correctness of reinnervation and function recovery. Conclusions: Despite previous, positive data on the speed and quantity of axonal regeneration, nimodipine and FK506 do not improve the final functional outcome of motoric reinnervation in rats.